2014
DOI: 10.2903/j.efsa.2014.3821
|View full text |Cite
|
Sign up to set email alerts
|

Tracing of food items in connection to the multinational hepatitis A virus outbreak in Europe

Abstract: In May 2013, Germany reported cases of hepatitis A virus (HAV) genotype IA infection in persons with a travel history and Italy reported a national increase in the number of HAV cases and declared an outbreak. Confirmed cases (outbreak strain KF182323) have been reported in Denmark, Finland, France, Germany, Ireland, Norway, the Netherlands, Poland, Sweden and the United Kingdom (331 in total). HAV contamination was detected in frozen mixed berries (14 lots) and mixed berry cakes/pastries (2 lots) in Italy, Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Due to the estimated low contamination level in foods and the low efficiency of common methods to recover viral RNA, the characterization by sequencing of detected viral RNA in food materials may often be more difficult than in human stool or blood samples (EFSA, 2014). Previously, we reported that the optimized direct lysis method applied in this study was significantly more efficient in recovering RNA of spiked model viruses on a selection of types of fruits compared to the ISO standard (Rajiuddin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the estimated low contamination level in foods and the low efficiency of common methods to recover viral RNA, the characterization by sequencing of detected viral RNA in food materials may often be more difficult than in human stool or blood samples (EFSA, 2014). Previously, we reported that the optimized direct lysis method applied in this study was significantly more efficient in recovering RNA of spiked model viruses on a selection of types of fruits compared to the ISO standard (Rajiuddin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, consumption of HAV contaminated fruit imported from endemic areas has been identified as the source of several large and sometimes multistate outbreaks of HAV in Europe (EFSA, 2014;Severi et al, 2015). For example, HAV contaminated frozen berries caused 1,589 cases including two deaths in 13 EU/EEA countries during 2013-2014 (Severi et al, 2015), 71 cases in four Nordic countries including Denmark during 2012-2013 (Lassen et al, 2013) and 14 cases in the Netherlands in 2017 (Mollers et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This outbreak, known as the largest HAV outbreak in Europe (74), led the European Commission to ask EFSA to coordinate an extensive tracing exercise. The aim was to identify the berries contaminated with the hepatitis A virus (mixed frozen berries), to trace them back to their place of production, and to find a point of contamination (37). Given the complexity of the event, the type of involved food items, and the epidemiological evidences available at the time of the exercise, the trace-back analysis could not identify a single point-source of contamination.…”
Section: A Persistent Polyclonal Outbreak Of Salmonellosis Associated With the Release Into The Market Of Contaminated Eggsmentioning
confidence: 99%